The given differential equation is ,
"yzdx+(x^2y-zx)dy+(x^2z-xy)dz=0"
We known that ,the necessary and sufficient condition of integrability of the given differential equation "Pdx+Qdy+Rdz=0" is
"...........(1)"
Now ,according to question,
"P=yz,Q=(x^2y-zx) \\ and \\ R=(x^2z-xy)"
Now ,
"\\frac{\\partial P}{\\partial y}=z \\ and \\ \\frac{\\partial P}{\\partial z}=y.""\\frac{\\partial Q}{\\partial x}=(2xy-z) \\ and \\ \\frac{\\partial Q}{\\partial z}=-x""\\frac{\\partial R}{\\partial x}=(2xz-y) \\ and \\ \\frac{\\partial R }{\\partial y}=-x"putting above all value in equation (1) ,we get ,
"yz(-x+x)+(x^2y-zx)\\{(2xz-y)-(y) \\}+(x^2z-xy) \\{(z)-(2xy-z)\\}"
"=0+2(x^3yz-x^2y^2-x^2z^2+xyz+x^2z^2-x^3yz-xyz+x^2y^2)=0"
Hence ,given differential equation is integrable.
To solve the given differential equation , we take
"x=constant. \\ \\implies \\ dx=0" .
"\\therefore \\ (x^2y-zx) dy+(x^2z-xy)dz=0"
"\\implies \\ x^2(ydy+zdz)-x(zdy+ydz)=0"
"\\implies \\ x^2(ydy+zdz)-xd(yz)=0"
On integrating ,we get
Where "\\phi" is a constant, it may be regarded as a function of "x."
Differentiating (2) w.r.t. x , y, and z we get,
"(xy^2dx+yx^2dy)+(xz^2dx+zx^2dz)-(yzdx+xzdy+xydz)=d\\phi"
On simplifying, we get
"(yx^2-xz)dy+(zx^2-xy)dz+yzdx+(xy^2+xz^2-2yz)dx=d\\phi \\ ...........(3)"
Since ,"yzdx+(yx^2-xz)dy+(zx^2-xy)dz=0 \\ (given \\ equation)" ,therefore equation (3) is,
"(xy^2+xz^2-2yz)dx=d\\phi \\ ........(4)"
Again from equation (2),
"\\implies \\ x^2y^2+x^2z^2-2xyz=2\\phi"
Now dividing both side by x ,we get
From equation (4) and (5) ,we get
On integrating ,we get
"logx^2+logk=log\\phi"
Where k is a constant.
"\\implies \\ log(x^2k)=log\\phi"
"\\implies \\ x^2k=\\phi"
Now ,putting the value of "\\phi" in equation (2) ,we get
"\\implies \\ xy^2+xz^2-2yz=2xk"
Comments
Leave a comment